Museum-Based Cultural Education as a Vehicle for Community Empowerment and Cultural Literacy in Indonesia - Nurhayati, Sri; Irama, Cindia; Putri, Alda Permata; Azizah, Ariestya Wan; Fauzan Hakim, Muhammad Iqbal; Jacob, Udeme Samuel; Boriboon, Gumpanat; Taufikin, Taufikin (IJTIMAIYA: Journal of Social Science and Teaching, 2025)
This study explores how museum-based cultural education serves as a vehicle for community empowerment and cultural literacy by analyzing the case of Museum Galeri Bahari Banuraja (Mugaba) in West Bandung, Indonesia. Using a qualitative case study approach, data were collected through direct observation, semi-structured interviews, and document analysis. Findings reveal that while Mugaba possesses rich maritime and Sundanese heritage collections, its educational program remains passive, with minimal interactive or participatory learning strategies. Limited use of local language, absence of storytelling practices, and weak digital outreach constrain its impact on youth engagement and cultural literacy development. However, the museum has stimulated local tourism and economic interest, suggesting latent potential for community revitalization. To address these challenges, the study recommends incorporating participatory storytelling, training guides in experiential pedagogy, curating intergenerational workshops, enhancing digital platforms, and establishing partnerships with local schools and artists. These strategies aim to reposition rural museums as inclusive, culturally grounded learning hubs. The study contributes to rethinking rural cultural institutions as dynamic platforms for education, identity formation, and sustainable development.